2020
DOI: 10.1111/idj.12542
|View full text |Cite
|
Sign up to set email alerts
|

Increased risks of dental caries and periodontal disease in Chinese patients with inflammatory bowel disease

Abstract: Objectives: Inflammatory bowel disease (IBD) may be associated with oral diseases, but few relevant studies have been reported in China. This study aimed to compare the prevalence, severity and extent of dental caries and periodontal disease in Chinese IBD patients and healthy controls. Materials and methods: In this cross-sectional study, questionnaires and oral examinations were completed for 389 IBD patients [265 with Crohn's disease (CD) and 124 with ulcerative colitis (UC)] and 265 healthy controls based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 40 publications
8
52
1
Order By: Relevance
“…This is in accordance with findings in the present study. Several studies have reported an increased DMFT index for CD patients [16][17][18][19]. It has been suggested that patients with CD may have a higher incidence of dental caries because of nutritional deficiencies, changes in salivary conditions, and oral microflora [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in accordance with findings in the present study. Several studies have reported an increased DMFT index for CD patients [16][17][18][19]. It has been suggested that patients with CD may have a higher incidence of dental caries because of nutritional deficiencies, changes in salivary conditions, and oral microflora [20].…”
Section: Discussionmentioning
confidence: 99%
“…Only three previous studies reported a significantly higher DMFT index in UC patients [ 17 19 ]. These studies were performed in China, Brazil, and Greece, so dissimilarities in comparison to a western European population cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited clinical studies were found assessing a connection between caries and gastrointestinal diseases, including studies of inflammatory gastrointestinal diseases [ 76 – 78 ]. A human clinical study (case-control) showed that pediatric participants with inflammatory bowel disease had significantly more caries and periodontal inflammation than healthy participants [ 76 , 77 ]. Similar results in an adult cohort has been shown previously [ 119 ].…”
Section: Discussionmentioning
confidence: 99%